Tapeçaria do texto: a dama e o unicórnio em Dora Ferreira da Silva - Goulart, Shirle (2021)
This research was developed from the images of some poems of the work of an important Brazilian writer and translator, Dora Ferreira da Silva, in which the texts and tapestries of Cluny entitled The Lady and the Unicorn were read approximately, in which the senses are recovered and amplified by the images of the poet's verses. The theoretical input is based, mainly, on studies about intertextuality, sacred, myths and imaginary. For this reason, due to the critical-theoretical bias, we appropriate the teachings of several authors and works, such as Gilbert Durand, The anthropological structures of the imaginary, Carl Gustav Jung, Relationship of analytical psychology with poetic art work, Julia Kristeva, Introduction to Seminanalysis, Ana Maria Lisboa de Mello, Poetry and Imaginary, Tiphaine Samoyault, Intertextuality, among others. Thus, we investigate art as being the means for the understanding of the human being about his own essence and reflect on the role of literature for the link between man and the spiritual world.